Art as Environmental Witness: Tharmapalan Tilaxan's Photographs of Ecological Crisis in Sri Lanka - Kirubalini, S. (University of Jaffna, Sri Lanka, 2026)
This paper examines how Northern Province-based freelance artist Tharmapalan Tilaxan’s photographic practice functions as a form of environmental witnessing, analyzed through the theoretical framework of “art as witness” in visual culture. The study focuses on two of his key projects: Gurunagar (2019), which addresses environmental degradation of fishing shores and marine biodiversity in Jaffna, including garbage disposal along the seashore, and The Story of Pallakkaddu Elephants / Garbage-Eating Elephants (2020), which highlights threats to elephants in Oluvil consuming garbage as food. In both cases, Tilaxan documented the sites in situ, observing ongoing ecological challenges, before exhibiting the works locally and later in galleries, thereby mediating between the environment, local communities, and broader audiences. The research addresses three central questions: How does Tilaxan document environmental issues through photography? What ecological and social issues are represented, and how are they framed? And how do local communities, environmentalists, government authorities, and international audiences respond, and what changes or continuities result? The objectives are to analyze the artistic strategies employed to render environmental degradation visible, explore the cultural and social narratives embedded in the imagery, and assess the impact of these works on public awareness and environmental discourse while maintaining aesthetic form. A qualitative methodology is adopted, combining iconographic and visual analysis with interviews of the artist and examination of media coverage. Findings indicate that Tilaxan’s photographs operate as both aesthetic objects and socio- environmental testimony, capturing ecosystem vulnerability and revealing tensions between human activity, conservation concerns, and ecological responsibility. Reactions vary, with local communities expressing ambivalence, environmentalists highlighting policy contradictions, and international audiences gaining heightened awareness. This selective and nuanced reception underscores the role of contemporary art in mediating environmental consciousness and highlights a gap in understanding how artistic documentation influences public perception, governmental authorities, and environmental discourse in Sri Lanka.
Keywords: Witness; Photography; Ecology; Crisis; Community response